Validating a nodal regression system for gastric cancer: An ancillary cohort study of the GASTRODOC trial. (October 2021) - Saragoni, Luca; Solaini, Leonardo; Marrelli, Daniele; Ambrosio, Maria Raffaella; Bencivenga, Maria; Tomezzoli, Anna; Milandri, Carlo; Terrinazzi, Valentina; Baiocchi, Gian Luca; Baronchelli, Carla; Foca, Flavia; Ercolani, Giorgio; et al.
Abstract: Background: To validate a nodal regression system for gastric cancer and to verify its impact on prognosis. Methods: This is an ancillary study which included 47 patients of the GASTRODOC trial. The dedicated pathologists of each Institute were invited to revise all the lymph nodes included in the surgical specimens in order to classify the regression according to the grading system proposed by Tsekrekos et al. The association of the nodal regression system and the clinico-pathological characteristics and prognosis were investigated. Results: According to the classification of Tsekrekos et al., there were 19 (40.4%) patients with grade a, 14 (29.8%) with grade b and 14 (29.8%) with grade c nodal regression. This regression system showed significant statistical associations with pathological N status (p < 0.001), residual tumor classification (p = 0.003) and Becker regression system (p = 0.011). At multivariable analysis only Tsekrekos' grading regression system was significantly associated with the PFS (HR 10.1, 95% CI 1.3–75.5; p = 0.025). Conclusions: The analyzed nodal regression system is significantly associated with Becker's regression system and it has a strong correlation with prognosis. Highlights: A nodal regression system for gastric cancer has been recently proposed. Its validation is an important step for its generalizability. This system was correlated with the T regression system. The proposed regression system displayed a significant correlation with progression free survival.